Chemical composition of craft hard cheeses from raw goat milk during the ripening process - V. Y. Sadvari; L. V. Shevchenko; N. M. Slobodyanyuk; S. V. Furman; D. V. Lisohurska; O. V. Lisohurska (Regulatory Mechanisms in Biosystems, 2024)
Craft goat cheeses have unique taste characteristics and are in high consumer demand. The production of goat cheeses from raw milk forms an authentic dynamic microbiome that determines their structure and chemical composition. Therefore, the research aimed to determine the physicochemical parameters of Caciotta and Canestrato goat cheeses during long-term ripening. Caciotta and Canestrato cheeses were made according to the recipe, and wheels weighing 2.3–2.5 kg were laid down for ripening for 24 and 12 months. During the ripening period of up to 24 months, Caciotta cheese lost moisture from 44.4% to 25.1%, which contributed to an increase in fat content from 27.0% to 36.5%, protein from 23.8% to 33.2%, and ash from 3.4% to 4.3%, while hardness decreased from 60.8% to 39.5%. The fat-to-protein ratio did not depend on the age of the Caciotta cheese and ranged from 1.10 to 1.24, reaching a maximum at 12 months of ripening. The structure of Caciotta cheese changed with age from plastic (10 days and 1 month) to slightly brittle (12 months) and brittle (24 months). The size, number, and arrangement of eyes in the cut of Caciotta cheese depended on the ripening period. As the Caciotta cheese aged, the rind hardened and changed color from milky to amber, and from 12 to 24 months, the degree of damage caused by the mite Acarus siro increased. The moisture content in Canestrato cheese from 10 days to 12 months of ripening decreased from 38.0% to 33.5%, the fat content increased by 3.8% at 12 months of ripening, while the protein and ash content did not depend on age. The hardness of Canestrato cheese during the ripening period fluctuated between 50.8–51.3% and the paste was characterized by a plastic homogeneous structure with varying sizes and locations of eyes depending on the ripening period. The rind of Canestrato cheese darkened from milky to amber with increasing ripening time and showed signs of damage by the mite A. siro starting from the age of 6 months. The results of the research on the dynamics of physicochemical processes can be used to determine the authenticity and criteria for the ripening of craft cheeses from unpasteurized goat milk.